2014
DOI: 10.4317/jced.51426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mandibular linear measurements obtained by cone beam computed tomography and digital calipers

Abstract: Objectives: Cone beam computed tomography (CBCT) is an innovative dental of imaging system characterized by rapid volumetric imaging with patient exposure to a single dose of radiation. The present study was carried out to compare the linear measurements obtained with CBCT and digital caliper in 20 mandibles from human cadavers. Study design: A total of 4800 linear measurements were measured between different mandibular anatomical points with CBCT and digital caliper. The real measurements were defined as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
4
11
1
Order By: Relevance
“…Overall, only three mesiodistal crown diameters had differences larger than 0.5 mm, which is considered the threshold for clinical acceptability [7,18]. This corresponds to 8% of the analysed dental distances (3 out of 12 distances x 3 techniques values), a value larger than that reported by Tarazona-Álvarez et al [6] who found only 5% of significant differences when comparing 20 linear distances obtained directly on dried mandibles and on their CBCT scans. Additionally, the current results well confirm that measurements involving the premolars are more variable than the other ones [4].…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tocontrasting
confidence: 44%
See 4 more Smart Citations
“…Overall, only three mesiodistal crown diameters had differences larger than 0.5 mm, which is considered the threshold for clinical acceptability [7,18]. This corresponds to 8% of the analysed dental distances (3 out of 12 distances x 3 techniques values), a value larger than that reported by Tarazona-Álvarez et al [6] who found only 5% of significant differences when comparing 20 linear distances obtained directly on dried mandibles and on their CBCT scans. Additionally, the current results well confirm that measurements involving the premolars are more variable than the other ones [4].…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tocontrasting
confidence: 44%
“…In general, the overestimation of calliper measurements vs. digital casts data is in line with the literature reports [18], while the comparison with CBCT data is more scattered. For instance, on dry mandibles, most of CBCT measurements were significantly smaller than those obtained by using the calliper [6].…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tomentioning
confidence: 99%
See 3 more Smart Citations